Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1055/s-2008-1063929
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B as an Immune Complex Disease

Abstract: Evidence has accumulated which indicates that several of the extrahepatic syndromes associated with HBV infection--the prodromal arthritis-dermatitis syndrome, systemic necrotizing vasculitis, and glomerulonephritis--result from immune complex-mediated injury; however, our understanding of their pathogenesis remains incomplete. Other disorders--essential mixed cryoglobulinemia and polymyalgia rheumatica--have also been linked to HBV, but these associations are more controversial. In most patients with HBV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 57 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Extrahepatic manifestations of HBV infection occur in 1% to 10% of patients, and include serum-sickness-like syndrome, acute necrotizing vasculitis (polyarteritis nodosa), membranous glomerulonephritis (MGN)85, and papular acrodermatitis of childhood (Gianotti-Crosti syndrome) 8687. Serum-sickness-like syndrome occurs in the setting of acute hepatitis B, often preceding the onset of jaundice 88.…”
Section: Pathophysiology / Serology / Signs and Symptomsmentioning
confidence: 99%
“…Extrahepatic manifestations of HBV infection occur in 1% to 10% of patients, and include serum-sickness-like syndrome, acute necrotizing vasculitis (polyarteritis nodosa), membranous glomerulonephritis (MGN)85, and papular acrodermatitis of childhood (Gianotti-Crosti syndrome) 8687. Serum-sickness-like syndrome occurs in the setting of acute hepatitis B, often preceding the onset of jaundice 88.…”
Section: Pathophysiology / Serology / Signs and Symptomsmentioning
confidence: 99%
“…Mixed cryoglobulinemia type I1 associated with HBV infection is a rare but known complication accompanied by immune complex vasculitis or by membranoproliferative glomerulonephritis [Dienstag, 1981;Ozawa et al, 19761. In chronic hepatitis B cryoglobulinemia is associated with disease activity [Lisker-Melman et al, 1989;Lev0 et al, 19771.…”
Section: Discussionmentioning
confidence: 99%
“…Although cardiac manifestations due to hepatitis have been recognized for a long time, there are few reports of myocarditis associated with HBV (10, 11). There are two hypotheses regarding HBV related myocarditis; one proposes an indirect mechanism with immune complexes (12), whereas the other proposes a direct myocardial cell injury by HBV. Some authors have reported that HBV proteins and nucleic acids were found in a number of non-hepatic tissues, including the myocardium (11,13).…”
Section: Discussionmentioning
confidence: 99%